A Cross-Country Analysis of ICT: Diffusion, Economic Growth and Global Competitiveness - Aniruddha Banerjee; Paul Rappoport; James Alleman (International Telecommunications Society (ITS), 2019)
Forty years ago, virtually the entire telecommunications sector was state owned, managed and controlled - owned, managed and controlled by the state since their inception. In the mid-1980s a movement towards privatization, liberalization and deregulation took hold. Now the sector has been privatized in most countries and subjected to regulatory reform. The major reform occurred in the late 1990s (Estache et al. 2006). Since then the internet and cellular-mobile industries have advanced significantly. Mobile service has exploded, particularly, in the developing world. This has changed the dynamics of the industry dramatically. The paper updates and expands the research on the contribution of Information and Telecommunications Technology's (ICT) on the growth of Gross Domestic Product (GDP) using cross-country analysis of selected countries. It follows the framework of Czernich (1991), et al.in it use of instrumental variables and Farhadi, et al. (2012) in its use of International Telecommunication Union's (ITU) ICT Development Index (IDI) but enhances the analysis by use of Global Competitiveness Index (GCI) and more recent data. It also uses the Conference Board Total Economic Database. This paper empirically evaluates the impact of ICT on economy growth in selected countries and vice versa. For the 2008-2017 period, it shows lack of evidence causality in both directions. This finding is in contrast to results obtained looking at earlier periods. A central question is, if these results hold going further, what changed? The paper is organized as follows: A brief Literature Review following this Introduction/Overview. It reviews the economic literature of Information and Telecommunications Technology's (ICT)impact on economic growth and development. The third section describes the data. The fourth section describes the methodology and; the results are in the fifth section. The final section presents Future Research and Remaining Questions.
Keywords: 330